Iatrogenic chest tube placement within the heart following a large pneumothorax - Shervin Zoghi, BS, BA; Cameron L. Brock, MD; Kwame Atsina, MD; Yasser G. Abdelhafez, MD, PhD; Fatma Sen, MD; Lorenzo Nardo, MD, PhD; Mohammad H. Madani, MD (Radiology Case Reports)
This case report describes an uncommon occurrence of cardiac injury and perforation resulting from chest tube placement. The patient, a 44-year-old female, presented to the ED with severe blunt force trauma following a pedestrian motor vehicle collision. Imaging revealed a large pneumothorax and multiple fractures. Pulsatile bleeding was observed during chest tube placement, and the tube’s tip was later found on CT of the thorax to be located within the heart. Although the patient recovered by postoperative day 13 and was subsequently discharged, this case highlights the importance of performing this procedure under image-guidance, along with elucidating the critical role of serial thorough clinical evaluations and prompt imaging for early detection and management of complications.